Enhancing Students’ Understanding of Statistics through the Use of Teaching Aids at SMP Negeri 2 Sabang - Moulianur Moulianur (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2025)
This study aims to improve students’ numeracy skills through the use of the Smart Stairs media in the statistics topic for Grade VIII students at SMP Negeri 2 Sabang in the 2024/2025 academic year. Smart Stairs is a three-dimensional staircase-shaped teaching aid designed to help students understand the concept of units of length and their conversions in a concrete way. This research is a Classroom Action Research (CAR) conducted in two cycles. Data collection techniques included observation, documentation, and validation questionnaires. The results showed an increase in student engagement and understanding during the learning process. In the first cycle, the percentage of active student participation was 44.44%, which increased to 88.88% in the second cycle. These results indicate that the use of Smart Stairs media can effectively enhance students’ numeracy skills and make mathematics learning more engaging, active, and meaningful.Keywords: Numeracy, Smart Stairs Media, Statistics, Teaching Aids, Mathematics Learning